2008
DOI: 10.5551/jat.e536
|View full text |Cite
|
Sign up to set email alerts
|

Pitavastatin Improves Serum Resistin Levels in Patients with Hypercholesterolemia

Abstract: Aim: Resistin in serum is associated with high risk in patients with atherosclerosis. This clinical study aimed to investigate whether pitavastatin can regulate the serum level of resistin, together with levels of other inflammatory cytokines and adipocytokines. Methods: Forty two outpatients (mean age 65.2 12.6 yr, M/F: 21/21) with hypercholesterolemia were administered 2 mg of pitavastatin and serum levels of resistin, together with serum levels of adiponectin, leptin, TNF-alpha and hsCRP, were measured befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
1
6
0
1
Order By: Relevance
“…3,81,82 Regardless, pitavastatin administration has been found to significantly decrease human serum resistin levels. 83 This effect of lowering resistin was also measured in a human breast cancer cell line. 84 In that study, pitavastatin inhibited the proliferation and suppressed the nuclear expression of NF-κB p65 induced by TNF-α, an inflammatory pathway that contributes to insulin resistance.…”
Section: Review Diabetesmentioning
confidence: 96%
“…3,81,82 Regardless, pitavastatin administration has been found to significantly decrease human serum resistin levels. 83 This effect of lowering resistin was also measured in a human breast cancer cell line. 84 In that study, pitavastatin inhibited the proliferation and suppressed the nuclear expression of NF-κB p65 induced by TNF-α, an inflammatory pathway that contributes to insulin resistance.…”
Section: Review Diabetesmentioning
confidence: 96%
“…These observations suggest that resistin plays a role in the development of CAD. Moreover, we 10) and others 11,12) reported that serum resistin levels correlate with plasma C-reactive protein (CRP) levels, thus suggesting a link between resistin and inflammation; however, studies investigating the association between resistin levels and cardiovascular events are scarce. Therefore, the present study was performed to elucidate the associations of pre-procedural serum resistin levels with cardiovascular events and angiographic restenosis in patients with CAD undergoing elective percutaneous coronary intervention (PCI).…”
Section: Introductionmentioning
confidence: 96%
“…Pitavastatin significantly has reduced serum resistin levels from 17.1±9.9 to 15.2±10.0 ng/ml following 12 weeks of therapy, which did not significantly correlate with a decrease in total cholesterol and LDL-cholesterol levels. Therefore, this reduction can be regarded as an important pleiotropic effect of pitavastatin to prevent the progression of atherosclerosis (Ohbayashi, 2008). Krassas et al (2005) have investigated resistin levels in hyperthyroid patients before and after restoration of thyroid function: relationship with body weight and body composition.…”
Section: Effect Of Drugs On Resistin Levelsmentioning
confidence: 99%
“…This confirmed that resistin concentrations were associated with systemic inflammation (Wen-lan et al, 2007). In an other study Chu et al;2008 have investigated plasma resistin levels association with myocardium injury in patients with acute coronary syndrome. Their investigation have occured the 39 patients with acute coroanry syndrome (ACS) and 26 age-healthy subjects.…”
Section: Effect Of Drugs On Resistin Levelsmentioning
confidence: 99%